Thrombin-Inhibiting Nanoparticles Rapidly Constitute Versatile and Detectable Anticlotting Surfaces - Myerson, Jacob Wheatley (Nanotechnology, 2014)
Restoring an antithrombotic surface to suppress ongoing thrombosis is an appealing strategy for treatment of acute cardiovascular disorders such as erosion of atherosclerotic plaque. An antithrombotic surface would present an alternative to systemic anticoagulation with attendant risks of bleeding. We have designed thrombin-targeted nanoparticles that bind to sites of active clotting to extinguish local thrombin activity and inhibit platelet deposition while exhibiting only transient systemic anticoagulant effects. Perfluorocarbon nanoparticles (PFC NP) were functionalized with thrombin inhibitors (either PPACK or bivalirudin) by covalent attachment of more than 15,000 inhibitors to each PFC NP. Fibrinopeptide A ELISA demonstrated that thrombin-inhibiting NPs prevented cleavage of fibrinogen by both free and clot-bound thrombin. Magnetic resonance imaging confirmed that a layer of thrombin-inhibiting NPs prevented growth of clots in vitro. Thrombin-inhibiting NPs were administered in vivo to C57BL6 mice subjected to laser injury of the carotid artery. NPs significantly delayed thrombotic occlusion of the artery, whereas an equivalent bolus of free inhibitor was ineffective. For thrombin-inhibiting NPs, only a short-lived (~10 minutes) systemic effect on bleeding time was observed, despite prolonged clot inhibition. Imaging and quantification of in vivo antithrombotic NP layers was demonstrated by magnetic resonance imaging (MRI) of the PFC NP. (19)F MRI confirmed colocalization of particles with arterial thrombi, and quantitative (19)F spectroscopy demonstrated specific binding and retention of thrombin-inhibiting NPs in injured arteries. The ability to rapidly form and image a new antithrombotic surface in acute vascular syndromes while minimizing risks of bleeding would permit a safer method of passivating active lesions than current systemic anticoagulant regimes.